Advanced Data Mining and Applications 6th International Conference, ADMA 2010, Chongqing, China, November 19-21, 2010, Proceedings, Part I - Cao, Longbing; Feng, Yong.; Zhong, Jiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Conference on Advanced Data Mining and Applications, ADMA 2010, held in Chongqing, China, in November 2010. 63 carefully reviewed regular papers and 55 revised short papers were presented. The papers are organized in topical sections on data mining foundations; data mining in specific areas; data mining methodologies and processes; and data mining applications and systems.
Data Mining Foundations -- Cost Sensitive Classification in Data Mining -- Web Users Access Paths Clustering Based on Possibilistic and Fuzzy Sets Theory -- Discriminative Markov Logic Network Structure Learning Based on Propositionalization and ? 2-Test -- EWGen: Automatic Generation of Item Weights for Weighted Association Rule Mining -- Best Clustering Configuration Metrics: Towards Multiagent Based Clustering -- On Probabilistic Models for Uncertain Sequential Pattern Mining -- Cube Based Summaries of Large Association Rule Sets -- A Perceptron-Like Linear Supervised Algorithm for Text Classification -- Research on Time Series Forecasting Model Based on Moore Automata -- A Clustering Algorithm FCM-ACO for Supplier Base Management -- Nearest Neighbour Distance Matrix Classification -- Classification Inductive Rule Learning with Negated Features -- Fast Retrieval of Time Series Using a Multi-resolution Filter with Multiple Reduced Spaces -- DHPTID-HYBRID Algorithm: A Hybrid Algorithm for Association Rule Mining -- An Improved Rough Clustering Using Discernibility Based Initial Seed Computation -- Fixing the Threshold for Effective Detection of Near Duplicate Web Documents in Web Crawling -- Topic-Constrained Hierarchical Clustering for Document Datasets -- Discretization of Time Series Dataset Using Relative Frequency and K-Nearest Neighbor Approach -- MSDBSCAN: Multi-density Scale-Independent Clustering Algorithm Based on DBSCAN -- An Efficient Algorithm for Mining Erasable Itemsets -- Discord Region Based Analysis to Improve Data Utility of Privately Published Time Series -- Deep Web Sources Classifier Based on DSOM-EACO Clustering Model -- Kernel Based K-Medoids for Clustering Data with Uncertainty -- Frequent Pattern Mining Using Modified CP-Tree for Knowledge Discovery -- Spatial Neighborhood Clustering Based on Data Field -- Surrounding Influenced K-Nearest Neighbors: A New Distance Based Classifier -- A Centroid k-Nearest Neighbor Method -- Mining Spatial Association Rules with Multi-relational Approach -- An Unsupervised Classification Method of Remote Sensing Images Based on Ant Colony Optimization Algorithm -- A Novel Clustering Algorithm Based on Gravity and Cluster Merging -- Data Mining in Specific Areas -- Evolution Analysis of a Mobile Social Network -- Distance Distribution and Average Shortest Path Length Estimation in Real-World Networks -- Self-adaptive Change Detection in Streaming Data with Non-stationary Distribution -- Anchor Points Seeking of Large Urban Crowd Based on the Mobile Billing Data -- Frequent Pattern Trend Analysis in Social Networks -- Efficient Privacy-Preserving Data Mining in Malicious Model -- Analyze the Wild Birds$1 (BMigration Tracks by MPI-Based Parallel Clustering Algorithm -- Formal Concept Analysis Based Clustering for Blog Network Visualization -- Finding Frequent Subgraphs in Longitudinal Social Network Data Using a Weighted Graph Mining Approach -- Weigted-FP-Tree Based XML Query Pattern Mining -- Privacy-Preserving Data Mining in Presence of Covert Adversaries -- Multiple Level Views on the Adherent Cohesive Subgraphs in Massive Temporal Call Graphs -- Combating Link Spam by Noisy Link Analysis -- High Dimensional Image Categorization -- Efficiently Mining Co-Location Rules on Interval Data -- Multiple Attribute Frequent Mining-Based for Dengue Outbreak -- A Top-Down Approach for Hierarchical Cluster Exploration by Visualization -- Distributed Frequent Items Detection on Uncertain Data -- Mining Uncertain Sentences with Multiple Instance Learning -- WeightLOFCC: A Heuristic Weight-Setting Strategy of LOF Applied to Outlier Detection in Time Series Data -- TGP: Mining Top-K Frequent Closed Graph Pattern without Minimum Support -- Research on Similarity Matching for Multiple Granularities Time-Series Data -- A Novel Algorithm for Hierarchical Community Structure Detection in Complex Networks -- Investigating Sequential Patterns of DNS Usage and Its Applications -- Key Issues and Theoretical Framework on Moving Objects Data Mining -- An Improved KNN Based Outlier Detection Algorithm for Large Datasets -- Some Developments of Determinacy Analysis -- A New Computational Framework for Gene Expression Clustering -- Forecasting Short-Term Trends of Stock Markets Based on Fuzzy Frequent Pattern Tree -- Inspired Rule-Based User Identification.s
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery; Computer Communication Networks